New amphora finds from Savaria (Pannonia): Preliminary report - A. Nagy, Anna (Rei Cretariae Romanae Fautorum Acta, 2015)
The aim of this research was to get a better knowledge of the trade of the ancient city of Savaria, a colonia along the Amber Route in Western-Pannonia in the light of new amphora finds.